SAT0035 RESPONSE TO ABATACEPT OF DIFFERENT PATTERNS OF INTERSTITIAL LUNG DISEASE IN RHEUMATOID ARTHRITIS: NATIONAL MULTICENTER STUDY OF 263 PATIENTS. (2nd June 2020) - Fernández-Díaz, C.; Castañeda, S.; Melero, R.; Loricera, J.; Ortiz-Sanjuán, F.; Juan-Mas, A.; Carrasco-Cubero, C.; Rodriguéz-Muguruza, S.; Rodrigez-Garcia, S.; Castellanos-Moreira, R.; Almodovar, R.; Aguilera Cros, C.; et al.
Abstract : Background: Interstitial Lung Disease (ILD) is a severe extraarticular manifestation of rheumatoid arthritis (RA). In this line, several radiological patterns of RA-ILD have been described: i) usual interstitial pneumonia (UIP), ii) nonspecific interstitial pneumonia (NSIP), iii) obliterating bronchiolitis, iv) organized pneumonia and mixed patterns. Abatacept (ABA) could be an effective and safe option for patients with RA-ILD, although the response in the different radiological patterns is not well defined. Objectives: Our aim was to assess the response to ABA in different radiological patterns of ILD. Methods: Observational retrospective multicenter study of RA-ILD treated with ABA. ILD was diagnosed by HRCT and classified by radiological patterns in 3 different subgroups of RA-ILD: a) UIP, b) NSIP and c) "other". ABA was used sc. or iv. at standard dose. We assessed: a) Dyspnoea (MMRC scale; significant variation ≥1); b) Respiratory function tests (significant changes ≥10% in FVC and DLCO); c) HRCT imaging; d) DAS28 e)prednisone dose. Variables were collected at months 0, 3, 6, 12 months and subsequently every 12 months until a maximum of 60 months. Results: We included 263 patients: 106 UIP, 84 NSIP and 73 others (150 women / 113 men), mean age 64.64±10 years. Total patients positive for RF or CCPA were 235 (89.4%) and 233 (88.6%), respectively. In 26 out of 263 patients, the development of ILD was closely related to the administration of sDMARDs (MTX n = 11 and LFN n = 1) or bDMARDs (ETN n = 5, ADA n = 4, CZP n = 2 and IFX n = 3). Patient characteristics are shown in table 1. Figure 1 shows the evolution of the cases with available data after a mean follow-up of 22.7±19.7 months. Mean DLCO and FVC remained stable in the 3 groups without statistically significant changes, and all the groups showed a statistically significant reduction in DAS28 and prednisone dose. Conclusion: ABA could be a good choice of treatment in patients with RA-ILD independently of the radiological pattern of ILD. Disclosure of Interests: Carlos Fernández-Díaz Speakers bureau: Brystol Meyers Squibb, Santos Castañeda: None declared, Rafael Melero: None declared, J. Loricera: None declared, Francisco Ortiz-Sanjuán: None declared, A. Juan-Mas: None declared, Carmen Carrasco-Cubero Speakers bureau: Janssen, MSD, AbbVie, Novartis, Bristol Myers Squibb, and Celgene, S, Rodriguéz-Muguruza: None declared, S. Rodrigez -Garcia: None declared, R. Castellanos-Moreira: None declared, RAQUEL ALMODOVAR Speakers bureau: Abbvie, Celgene, Janssen, Lilly, Novartis, Pfizer., CLARA AGUILERA CROS: None declared, Ignacio Villa-Blanco Consultant of: UCB, Speakers bureau: Novartis, MSD, Lilly, Sergi Ordoñez: None declared, Susana Romero-Yuste: None declared, C. Ojeda-Garcia: None declared, Manuel Moreno: None declared, Gemma Bonilla: None declared, I. Hernández-Rodriguez: None declared, Mireia Lopez Corbeto: None declared, José Luis Andréu Sánchez: None declared, Trinidad Pérez Sandoval: None declared, Alejandra López Robles: None declared, Patricia Carreira Grant/research support from: Actelion, Roche, MSD, Consultant of: GlaxoSmithKline, VivaCell Biotechnology, Emerald Health Pharmaceuticals, Boehringer Ingelheim, Roche, Speakers bureau: Actelion, GlaxoSmithKline, Roche, Natalia Mena-Vázquez: None declared, C. Peralta-Ginés: None declared, ANA URRUTICOECHEA-ARANA: None declared, Luis Marcelino Arboleya Rodríguez: None declared, J. Narváez: None declared, DESEADA PALMA SANCHEZ: None declared, Olga Maiz-Alonso: None declared, J. Fernández-Leroy: None declared, I. Cabezas-Rodriguez: None declared, Ivan Castellví Consultant of: Boehringer Ingelheim, Actelion, Kern Pharma, Speakers bureau: Boehringer Ingelheim, Actelion, Bristol-Myers Squibb, Roche, A. Ruibal-Escribano: None declared, JR De Dios-Jiménez Aberásturi: None declared, Paloma Vela-Casasempere: None declared, C. González-Montagut Gómez: None declared, J M Blanco: None declared, Noelia Alvarez-Rivas: None declared, N. Del-Val: None declared, M. Rodíguez-Gómez: None declared, Eva Salgado-Pérez: None declared, Carlos Fernández-López: None declared, E.C. Cervantes Pérez: None declared, A. Devicente-DelMas: None declared, Blanca Garcia-Magallon Consultant of: MSD, Speakers bureau: Pfizer, Amgen, Celgene, MSD, Cristina Hidalgo: None declared, Sabela Fernández: None declared, R. López-Sánchez: None declared, Edilia García-Fernández: None declared, S. Castro: None declared, P. Morales-Garrido: None declared, Andrea García-Valle: None declared, Rosa Expósito: None declared, L. Exposito-Perez: None declared, Lorena Pérez Albaladejo: None declared, Ángel García-Aparicio: None declared, Miguel A González-Gay Grant/research support from: Pfizer, Abbvie, MSD, Speakers bureau: Pfizer, Abbvie, MSD, Ricardo Blanco Grant/research support from: AbbVie, MSD, and Roche, Speakers bureau: AbbVie, Pfizer, Roche, Bristol-Myers, Janssen, and MSD